Clinical importance of pharmacogenetic polymorphisms affecting drug metabolism: psychopharmacology and pain - Stingl (formerly Kirchheiner), Julia (Henry Stewart Talks, 2007)
Pharmacogenetic polymorphisms, Biotransformation and clinical outcome, Consequences of genotyping, Feasibility for genotyping in antidepressant drug treatment, Polymorphic cytochrome P450 enzyme CYP2D6, Feasibility for genotyping in pain treatment, CYP2C9, CYP2D6 and nonsteroidal analgetic drugs
Archived at 2018/12/10